A NUTS-2 European Union interregional system of Social Accounting Matrices for the year 2017: The RHOMOLO V4 dataset - Abián García-Rodríguez; Nicholas Lazarou; Giovanni Mandras; Simone Salotti; Mark Thissen; Erwin Kalvelagen (European Commission, Joint Research Centre (JRC), 2023)
We describe the procedure used to construct a set of interregional NUTS-2 European Union Social Accounting Matrices for the year 2017, using official Eurostat national and regional account data, and auxiliary data on business and interregional trade flows derived from transport survey data. This procedure builds on the one presented by Thissen et al. (2019) for the year 2013. The new dataset is described by presenting some relevant features and the results of some characteristic simulations obtained with a new version of t he RHOMOLO model, referred to as RHOMOLO V4, based on the new 2017 data.
Keywords: C82; E16; R15; F14; F47; 330; Regional data; Input-Output; social accounting matrices; trade flows; general equilibrium